Air Defense Identification Zone (ADIZ) in the light of Public International Law - Papp, Zoltán (Pécs journal of international and European law, 2015)
The Air Defense Identification Zone (ADIZ) is established to serve the national security interests of the state. Maintaining ADIZ becomes fundamentally relevant from the perspective of international law when such a zone extends into airspace suprajacent to international waters. Materially, two considerations are most relevant in terms of ADIZ conforming to international law, both potentially creating a conflict with ADIZ rules: Contracting Parties to the Chicago Convention on International Civil Aviation have delegated rule-making powers to enact rules of the air with a view to safeguarding the safety of air traffic in international airspace to the ICAO Council. Furthermore, in international airspace the state of registry generally enjoys exclusive jurisdiction with respect to the aircraft carrying its national mark. In this paper ADIZ will be deemed as exercising jurisdiction over extraterritorial acts by the state maintaining ADIZ; hence, the prescriptive and enforcement distinction adds an additional layer to the analysis of the international legal context of ADIZ. The response to as to how ADIZ fits in the international legal framework may differ depending on whether one seeks to identify permissive rules of international law related to the maintenance of ADIZ in international airspace or the non-existence of prohibitive rules sufficient to justify conformance with international law.